Relationship between Mismatch Repair (MMR) Status and Chemotherapy Response in Colorectal Carcinoma - Desmeradd, Soraya Sagita; Rusminan, Suly Auline; Kartika, Ika; Bahar, Erial (Majalah Patologi Indonesia, 2025)
Background Colorectal carcinoma has several pathways that play a role in normal colonic mucosa development into carcinoma, one of microsatellite instability (MSI) pathway. This pathway results from a deficiency in one of the MMR proteins that normally repair genome damage, leading to microsatellite instability high (MSI-H) and excessive mutations. MSI-H is closely associated with Lynch syndrome and often experiences resistance to chemotherapy treatment, one of which is 5-fluorouracil (5-FU), so it is necessary to conduct initial screening in colorectal carcinoma to assess MMR status on patient with Lynch syndrome . This study aims to see relationship between MMR status and chemotherapy response in colorectal carcinoma. Methods This study is cross sectional study using 30 archival block and slaid samples of all colorectal carcinoma cases from hemicolectomy and biopsy results that have been histopathologically diagnosed in Anatomic Pathology Section of Faculty of Medicine Unsri/RSMH Palembang January 2017-December 2021. Each sample was immunohistochemically stained using four antibodies namely anti-MLH1, anti-MSH2, anti-MSH6 and anti-PMS2 (ventana). Interpretation was qualitative by assessing cell positivity. Categorized into intact and missing with cut-off point value of >10% positive declared intact. MMR deficiency was considered if there was loss of cell positivity, at least one MMR CPI marker and MMR proficiency if all MMR CPI were intact. Analysis of relationship between MMR status and chemotherapy response was performed using Fisher's exact test. Results Fisher's exact test showed an association between MMR status and chemotherapy response. The results were significantly significant with p-value of 0.045 where MMR deficiency status had a 6 times chance of not responding to chemotherapy compared to MMR proficiency. There was no association between MMR status and age, gender, histopathological subtype and tumor location with p-values of 0.139, 1.000, 0.657 and 0.174 respectively. Conclusion There was a significant association between MMR status and chemotherapy response.